Let’s Talk about the Animals – Taking the Outcomes of Animal Models of Human Emotion and Affective Behavior Back to Understanding Animal Minds and Emotions - Gaspar, Augusta D. (Journal of applied animal ethics research, 2023)
The socioemotional lives of animals have been brought to light over the years by studies seeking to address specific topics in animal emotion, cognition and behavior. Breakthrough information has been provided by field work with natural communities, and notable advances have stemmed from non-invasive research with captive animals and from laboratory work entailing varying degrees of invasiveness. But there is a source of information on animals that has not always been integrated in the knowledge on animals’ emotional lives: the outputs of studies where animals served as models of human emotional processes but that were seldom published as literature on animals. This article proposes an integrated view whereby the vast amount of information amassed by the brain and behavioral sciences over the course of the last 30 years on the affective experiences of animals, their triggers, biomarkers and behavioral correlates is fully integrated in an account of animal emotions. Topics where this knowledge can accommodate further integration from studies with animals models of the human mind are the parental care and different types of affective bonds; the experience of empathic reactions, the association between emotions, expressive behavior and affective bonds, and conscience. Fostering further connection between these neuroscience and behavioral studies might contribute to 1) widening the breath of measures used in assessing the well-being of animals, 2) widening criteria used by ethical committees considering studies with animals, and 3) to review some common practices that by those who have key roles in the management of wild or captive animals.